Pathologists Overseas: A volunteer-based model for building sustainable, high-quality pathology and laboratory medicine services in low- and middle-income countries - Glynn, Emily H.; Nelson, Ann Marie; Tesfazghi, Merih; Harb, Roa; Amukele, Timothy (Frontiers in Medicine, 2022)
For thirty years Pathologists Overseas (PO) has worked in low- and middle-income countries (LMICs) to provide affordable, sustainable, and high-quality PALM services through strategic partnerships and the efforts of our large volunteer network. We address low quality diagnostic services by targeting the 3 pillars of PALM quality: human resources, systems, and quality and accreditation. To improve human resource capacity, PO and our partnering organizations provide virtual continuing education to pathologists and laboratory professionals in these countries. To improve systems, we provide laboratory information system installation and implementation support. Lastly, to improve quality and help laboratories progress toward accreditation, we support an external quality assurance program for laboratories in LMICs. As a relatively small organization, PO demonstrates that a network of dedicated volunteers, in partnership with corporations and professional organizations, can initiate sustainable change in the quality of PALM services in LMICs by focusing efforts on the core components of laboratory quality.